2011
DOI: 10.1007/s11426-011-4250-x
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the studies of low-molecular mass gelators with unusual properties

Abstract: This article is intended to provide an overview of recent progress in the studies of cholesterol-based low-molecular mass gelators (LMMGs) with unusual properties, in particular, gelation and selective gelation at room temperature, gel emulsions and gel film formation, etc. Potential applications of the LMMGs in spilled oil collection and water purification are briefly presented.gelation at room temperature, selective gelation, gel emulsions, gel films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 72 publications
(161 reference statements)
0
23
0
Order By: Relevance
“…LMMG / 5 LMOGs are being found that can gel solvents under other conditions such as photo irradiation, sonication, chemical or electrical stimuli. 29 Polymer (macromolecular) gels.…”
Section: Colloidal Gelsmentioning
confidence: 99%
“…LMMG / 5 LMOGs are being found that can gel solvents under other conditions such as photo irradiation, sonication, chemical or electrical stimuli. 29 Polymer (macromolecular) gels.…”
Section: Colloidal Gelsmentioning
confidence: 99%
“…Appropriately designed gelators, i.e. , decorated with suitable functional groups, can be programmed for example to be responsive to external stimuli such as light, mechanical stress, pH, ionic strength, metal ions, or anions [ 29 , 30 , 31 , 32 , 33 , 34 ]. In most cases, a change on a molecular level results directly in a change of macroscopic properties of the whole system.…”
Section: Introductionmentioning
confidence: 99%
“…As a recently developed medium for crystal growth, supramolecular gels derived from low‐molecular‐mass gelators (LMMGs), are a typical class of soft materials in which gelator molecules can be assembled into dynamic 3D networks via cooperative noncovalent interactions . The gel matrix commonly entraps solvent molecules and prevents the macroscopic flow of the solvent within its networks.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, structures of LMMGs can be tailored for adapting to different solvents including water and organic solvents. Thus, gel rheology or the surface functionality of gel fibers can also be altered accordingly, if needed . On the contrary, gelators for conventional gels are polymeric or clay‐like materials such as gelatine, agarose, polyacrylamide, or silica .…”
Section: Methodsmentioning
confidence: 99%